Tatbiqu Kitabi Durusi al-Lughati al-‘Arabiyyati al-Juz’i ats-Tsani fi Ta‘limi al-Lughati al-‘Arabiyyati li-Tullabi as-Saffi ats-Tsamini bi-Ma‘hadi Nuri al-Hakim al-‘Ashri Tembung: Implementation of Durus Al-Lughah Al-‘Arabiyyah Volume II in Arabic Language Learning for Eighth-Grade Students at Nurul Hakim Modern Islamic Boarding School Tembung - Nur Azizah Putri; Khoirul Jamil (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
Arabic language learning in modern Islamic boarding schools plays a vital role in equipping students with the ability to comprehend Arabic texts and to communicate both orally and in writing. However, in practice, Arabic language instruction still faces several challenges, including differences in students’ basic competencies in vocabulary mastery, grammatical knowledge (qawāʿid), and reading comprehension, as well as limitations in instructional media. These conditions require the availability of systematic teaching materials and appropriate instructional methods to ensure effective learning. Therefore, this study aims to describe the implementation of the textbook Durūs al-Lughah al-ʿArabiyyah, Volume II, by Imam Zarkasyi and Imam Syubani in Arabic language instruction for eighth-grade students at the Modern Islamic Boarding School Nurul Hakim Tembung. This textbook was selected due to its systematic structure, which begins with basic vocabulary and grammar and is complemented by exercises that support the development of language skills. This study employs a descriptive qualitative approach through field research and library research. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data display, and verification techniques. The findings indicate that Arabic language learning for eighth-grade students using the textbook Durūs al-Lughah al-ʿArabiyyah was implemented through lecture, question-and-answer, and group-work methods to facilitate students’ understanding of vocabulary, grammar, and the language exercises (tamrīn lughawī) contained in the textbook. Thus, the implementation of this textbook is considered fairly adequate; however, it still requires innovation in instructional methods and learning media to achieve more optimal learning outcomes. Keywords: Arabic Language Learning, Book Durusul Lughah Al-‘Arabiyyah, Implementation